Achieving Paris Agreement temperature goals requires carbon neutrality by middle century with far-reaching transitions in the whole society - Huang, Meng-Tian; Zhai, Pan-Mao (Advances in climate change research, 2021)
The concept of carbon neutrality is much emphasized in IPCC Spatial Report on Global Warming of 1.5 °C in order to achieve the long-term temperature goals as reflected in Paris Agreement. To keep these goals within reach, peaking the global carbon emissions as soon as possible and achieving carbon neutrality are urgently needed. However, global CO2 emissions continued to grow up to a record high of 43.1 Gt CO2 during 2019, with fossil CO2 emissions of 36.5 Gt CO2 and land-use change emissions of 6.6 Gt CO2. In such case, the global carbon emissions must drop 32 Gt CO2 (7.6% per year) from 2020 to 2030 for the 1.5 °C warming limit, which is even larger than the COVID-induced reduction (6.4%) in global CO2 emissions during 2020. Recently, China has announced scaling up its national commitments, aiming to peak its CO2 emissions before 2030 and achieve carbon neutrality before 2060. Achieving these goals requires rapid and far-reaching transitions in the whole society. On the one hand, deeper emissions reduction in all sectors includes decarbonization of energy, electrification, increasing share of renewables, energy efficiency, sustainable land management, decarbonization of transport, reducing food loss and waste, as well as behavior and lifestyles changes. On the other hand, possible actions by removing CO2 from the atmosphere involves enlarging land and ocean net carbon sink, CO2 removal technologies (such as Bioenergy with carbon capture and storage), and CO2 capture, utilization and storage technologies, but should be caution for their scales and tradeoffs.